Can anybody evaluate the following sum for me? $$\sum\limits_{n=2}^\infty(-1)^n\left(\frac{\psi(n)}{n}-\frac{\Lambda(n)}{2n}\right),$$ where $\psi(n)$ is the Chebyshev function and $\Lambda(n)$ is the Von Mangoldt function.

I tried using the fact that Chebyshev function is summatory Von Mangoldt function but it did not help. I am only interested in the numerical value.


I tried to find an exact closed form for this sum, but one part is left as a fairly rapidly converging series. The original sum is not entirely convergent either but may be normalized to a convergent value. $$ S= \sum_{k=2}^{\infty}{(-1)^k}\left(\frac{\psi(k)}{k} - \frac{\Lambda(k)}{2k}\right) = \sum_{k=2}^{\infty}\frac{(-1)^k}{k}\left(\psi(k) - \frac{\Lambda(k)}{2}\right) $$ This inner term becomes equal to the Normalized Chebyshev Function $\psi_0(k)$. As this has the closed form. $$ \psi_0(x)=x-\sum_\rho{\frac{x^\rho}{\rho}}-\ln(2\pi)-\frac{1}{2}\ln\left(1-x^{-2}\right) \\ \frac{\psi_0(x)}{x}=1-\sum_\rho{\frac{x^{\rho-1}}{\rho}}-\frac{\ln(2\pi)}{x}-\frac{1}{2x}\ln\left(1-x^{-2}\right) $$ Where $\rho$ is a non-trivial zero of the Riemann Zeta Function. This implies that the initial sum is: $$ S= \sum_{k=2}^{\infty}{(-1)^k}\frac{\psi_0(k)}{k} \\ S= \sum_{k=2}^{\infty}{(-1)^k}\left(1-\sum_\rho{\frac{k^{\rho-1}}{\rho}}-\frac{\ln(2\pi)}{k}-\frac{1}{2k}\ln\left(1-k^{-2}\right)\right)\\S= \sum_{k=2}^{\infty}{(-1)^k}-\sum_{k=2}^{\infty}{(-1)^k}\sum_\rho{\frac{k^{\rho-1}}{\rho}}-\sum_{k=2}^{\infty}{(-1)^k}\frac{\ln(2\pi)}{k}-\sum_{k=2}^{\infty}{(-1)^k}\frac{1}{2k}\ln\left(1-k^{-2}\right) $$ The second sum may be evaluated by interchanging the order of summation: $$ \sum_{k=2}^{\infty}{(-1)^k}\sum_\rho{\frac{k^{\rho-1}}{\rho}}=\sum_\rho\frac{1}{\rho}\sum_{k=2}^{\infty}{(-1)^k}{k^{\rho-1}}\\=-\sum_\rho{\frac{\eta(1-\rho)-1}{\rho}}=\sum_\rho{\frac{1}{\rho}}=\frac{\gamma}{2}+1-\frac{1}{2}\ln(4\pi) $$ The third is just a form of the natural logarithm of 2: $$ \sum_{k=2}^{\infty}{(-1)^k}\frac{\ln(2\pi)}{k}=\ln(2\pi)\sum_{k=2}^{\infty}\frac{(-1)^k}{k}=\ln(2\pi)(\ln(2)-1) $$ The last sum does not seem to have a nice closed form but gives a decent approximation of: $$ \sum_{k=2}^{\infty}{(-1)^k}\frac{1}{2k}\ln\left(1-k^{-2}\right)\approx-0.05773249... $$ The first sum gives either a value of 1 or 0 depending on an even or odd partial sum, i.e. Grandi's Series. This makes the initial sum divergent. Grandi's Series has the normalization of $\frac{1}{2}=\eta(0)$, giving three possible sums.

As a lower bound: $$ S_1=0-\frac{\gamma}{2} -1 +\frac{\ln(4\pi)}{2}-\ln(2\pi)(\ln(2)-1)-\sum_{k=2}^{\infty}{(-1)^k}\frac{1}{2k}\ln\left(1-k^{-2}\right)\\=-1-\frac{\gamma}{2} -\frac{\ln(\pi)}{2}-\ln(2\pi)\ln(2)-\sum_{k=2}^{\infty}{(-1)^k}\frac{1}{2k}\ln\left(1-k^{-2}\right)\\ \approx -1-\frac{\gamma}{2} -\frac{\ln(\pi)}{2}-\ln(2\pi)\ln(2)+0.05773249...\approx -.5293209... $$ For an upper bound: $$ S_2=S_1+1\approx .40679021... $$ As the normalized sum: $$ S_3=S_1+\frac{1}{2}\approx-.02932097... $$

The normalized value is the most correct one, as the other two are just divergent messes, but sadly the last natural logarithm sum doesn't seem to have a nice closed form.


Just partial answer. Let $$f(k)=\sum\limits_{n=2}^k(-1)^n\left(\frac{\psi(n)}{n}-\frac{\Lambda(n)}{2n}\right).$$ The values of $f$ are

  • $f(500) = 0.4723238355$
  • $f(1000) = 0.4690203884$
  • $f(1500) = 0.4737698493$
  • $f(2000) = 0.4692923722$
  • $f(2500) = 0.4703526128$
  • $f(3000) = 0.4708612774$
  • $f(3500) = 0.4683767275$
  • $f(4000) = 0.4693891317$
  • $f(4500) = 0.4701923562$
  • $f(5000) = 0.4704750068$
  • ...

You're asking for $\lim_{k \rightarrow \infty} f(k)$, but I even don't know how to prove that this series is convergent or not.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.